The impact of multi-cycle water invasion on underground gas storages and its controlling factors - Liao, Wei; Zhang, Shijie; Lv, Mingyang; Zhao, Yifeng; Yan, Huilin; Shi, Guoliang; Nooraiepour, Mohammad; Ma, Lin; Spasennykh, Mikhail; Song, Zezhang (Frontiers in Earth Science, 2025)
Underground gas storage (UGS) facilities are essential for supply security and peak-shaving in natural gas systems, yet their sustainability is limited by an incomplete understanding of water invasion. This study examines the Hutubi UGS, the largest facility in China and the first serving the West-East Gas Pipeline II, to identify the controls of water invasion under intensive injection-withdrawal cycles. Using geological data from the second member of the Ziniquanzi Formation and multi-cycle injection-withdrawal records, we combined three-dimensional geological modeling with numerical simulation to assess aquifer energy and invasion pathways. The reservoir functions as a weak water-drive system with limited aquifer support. Water invasion is stratified and directional: high-permeability channels promote preferential migration in the western E1–2Z21 sub-reservoir, while localized bottom-water coning dominates in the E1–2Z22 sub-reservoir. Six factors act in concert to govern invasion: aquifer energy, structural boundaries, sedimentary facies, reservoir heterogeneity, physical properties, and pore structure. Together, they define a coupled mechanism that shapes the magnitude and spatial distribution of water invasion. This framework advances understanding of invasion dynamics in UGS and offers practical guidance for enhancing the long-term efficiency and sustainability of natural gas storage.